Anomalie temperatury powietrza w Lasach Doświadczalnych SGGW w Rogowie w latach 1924–2015 - Chojnacka-Ożga, Longina; Ożga, Wojciech (Leśne Prace Badawcze, 2018)
Meteorological measurements, that aim to monitor weather and climate conditions to aid research in changing forest ecosystems, have been conducted in Warsaw University of Life Sciences’ experimental forests in Rogów since 1924. Based on the long-term air temperature measurements, it can be demonstrated that in the years 1924–2015 anomalously cold months have occurred less often (ca. 3,2%) than anomalously warm months (ca. 4,5%). During the last 20 years, only one anomalously cold month was recorded (December 2010), whereas anomalously warm months occurred frequently (May 2002, July 1999, 2002, 2006, 2010, 2012, 2014, August 2002, 2015, September 1999, 2006, October 2000, 2001). We hypothesised that the more frequent anomalously warm months would constitute a trend in increasing air temperature for particular months between 1924–2015, but surprisingly a statistically significant trend was observed for all winter (XII–II) and spring months (III–IV) as well as the end of summer (VIII).